Targeting ataxia telangiectasia-mutated- and Rad3-related kinase (ATR) in PTEN-deficient breast cancers for personalized therapy - Al-Subhi, Nouf (Breast Cancer Res Treat, 2018)
PURPOSE: Phosphate and tensin homolog (PTEN), a negative regulator of PI3K signaling, is involved in DNA repair. ATR is a key sensor of DNA damage and replication stress. We evaluated whether ATR signaling has clinical significance and could be targeted by synthetic lethality in PTEN-deficient triple-negative breast cancer (TNBC). METHODS: PTEN, ATR and pCHK1(Ser345) protein level was evaluated in 1650 human breast cancers. ATR blockade by VE-821 was investigated in PTEN-proficient- (MDA-MB-231) and PTEN-deficient (BT-549, MDA-MB-468) TNBC cell lines. Functional studies included DNA repair expression profiling, MTS cell-proliferation assay, FACS (cell cycle progression & γH2AX accumulation) and FITC-annexin V flow cytometry analysis. RESULTS: Low nuclear PTEN was associated with higher grade, pleomorphism, de-differentiation, higher mitotic index, larger tumour size, ER negativity, and shorter survival (p values < 0.05). In tumours with low nuclear PTEN, high ATR and/or high pCHK1(ser345) level was also linked to higher grade, larger tumour size and poor survival (all p values < 0.05). VE-821 was selectively toxic in PTEN-deficient TNBC cells and resulted in accumulation of double-strand DNA breaks, cell cycle arrest, and increased apoptosis. CONCLUSION: ATR signalling adversely impact survival in PTEN-deficient breast cancers. ATR inhibition is synthetically lethal in PTEN-deficient TNBC cells. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10549-018-4683-4) contains supplementary material, which is available to authorized users.